On the Experimental Analysis of Temperature Influence on Stiffness of Reinforced Concrete Beams. (1st March 2015) - Kowalski, Robert; Glowacki, Michal; Abramowicz, Marian
Abstract : The paper presents results of experimental research whose main topic was determination of stiffness reduction in bent reinforced concrete beams in two cases: when only tensioned or only compressed zone was exposed to high temperature. Twenty four reinforced concrete beams with rectangular cross-section were prepared for the experiment. Eight groups of beams were prepared in total: 2 with reinforcement ratio - 0.44 and 1.13% x 2 levels of load - 50 or 70% of destructive force ensuring the constant value of bending moment in the centre part of heated beams x 2 static schemes. Three beams were used in each group. Significant cross-section stiffness reduction was observed in beams where the tensile zone was heated. This was due to considerable elongation of the bars where the steel load elongation summed up with the free thermal strain. In beams where the compressed zone was heated the stiffness reduction was observed only after the time where the tensile zone heated cross-sections were already destroyed.